THE ROLE OF THE COMMUNITY AND VILLAGE APPARATUS IN PREVENTING NARCOTICS ABUSE AMONG ADOLESCENTS IN KLAMBIR LIMA KEBUN VILLAGE, HAMPARAN PERAK DISTRICT, DELI SERDANG REGENCY - Suci Ramadani; Rahmayanti; Sofia Naliza Sitepu (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to examine the role of the community and village officials in preventing narcotics abuse among adolescents in Klambir Lima Kebun Village, Hamparan Perak District, Deli Serdang Regency. Narcotics abuse is a serious problem that can damage the younger generation and have a bad impact on the future of the nation. Therefore, preventing narcotics abuse among adolescents requires the active role of various parties, including the community and village officials. This study uses a qualitative approach with a descriptive method, which collects data through in-depth interviews with communities, village heads, and village officials who are directly involved in narcotics prevention activities. The results of the study show that the role of the community and village officials is very important in prevention efforts, which include raising awareness through socialization, the formation of youth empowerment groups, and stricter supervision of the environment. The community, especially parents and religious leaders, plays a role in providing education to adolescents about the dangers of narcotics, while village officials, including village heads and village officials, coordinate with relevant parties and ensure policies that support narcotics prevention. This research is expected to provide insight into the importance of collaboration between the community and village officials in preventing narcotics abuse and creating a safer environment for the younger generation.